PATHOMORPHOLOGICAL CHANGES IN ORGANS WITH A COMBINATION OF NEW CARONAVIRAL INFECTION (COVID-19) AND PNEUMOCONIOSIS IN WORKERS OF THE COAL INDUSTRY OF KUZBASS - Бондарев, Олег Иванович; Семенов, Дмитрий Евгеньевич; Лапий, Галина Анатольевна; Бугаева, Мария Сергеевна; Казицкая, Анастасия Сергеевна (Medicine in Kuzbass, 2020)
Objective – on the basis of pathomorphological data, to determine the pathogenetic significance in the thanatogenesis of a new coronavirus infection (COVID-19) in combination with pneumoconiosis in coal workers. Methods. A histological and morphometric examination of internal organs was carried out in miners with work experience of 20 years or more and in individuals from the control group. Autopsy material was obtained during 15 autopsy examinations of miners in the Kemerovo region. All the deceased under the heading clinical diagnosis had bilateral pneumonia, severe course. Nine had suspected viral lung disease (COVID-19). Results. The pathomorphological features of systemic damage to internal organs in pneumoconiosis of the lungs in combination with a new coronavirus infection (COVID-19) are shown. The morphology of changes in the endothelial cells of the vessels of the lungs, heart, liver, kidneys and brain as the main systemic trigger factor that triggers the main pathological processes in combined pathology is described. Conclusions. According to the totality of the revealed data (thickening and changes in the endothelial lining, the presence of periarterial and perivenular fibrosis, macrophage inflammatory reaction with inclusions of viral symplasts, pronounced hemorrhagic syndrome, stasis, sludge and thrombosis of the vessels of the microvasculature) pneumoconiotic changes in combination with the new coronavirus generalized nature, which is realized by the development of multiple organ failure.